PELATIHAN PEMBUATAN PERMAINAN MATEMATIKADAN SIMULASINYA DENGAN PERANGKAT LUNAK KOMPUTERUNTUK MENANAMKAN SIKAP POSITIF TERHADAPALAM SEKITAR BAGI GURU SEKOLAH DASARKORBAN BENCANA MERAPI - Wahyu Setyaningrum, dan Fitriana Yuli S., Ali Mahmudi, Sri Andayani, Kuswari Hernawati (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2012)
This activity aims to enhance knowledge, skills and motivation ofprimary school teachers in post-disaster Merapi in creating a mathematicalgame that utilizes the natural around Merapi to be used in the process oflearning mathematics so as to foster positive attitudes toward children's naturalsurroundings. Prior to implementation, the team conducted observations ofnatural objects around Merapi, which can be used for math games. Observationscarried out in SD Cangkringan 2, as a training location that is one of theprimary victim Mount Merapi eruptions.The activity has been carried out for 3 days, ie Friday-Sunday on 30September to 2 October 2011 with a total allocation of time is 24 hours. Placeof activity is in SD Cangkringan 2 and in computer laboratory of SMK MuhammadiyahCangkringan, which is located adjacent to the SD Cangkringan 2. Inthe activity, which was attended by 31 elementary school teachers in this Cangkringan,servant teams conduct lectures, practical training and workshops andpresentation of results. The training materials include: orientation of learningmathematics in primary schools continued with the media game in elementaryschool learning that can take advantage of natural surroundings, and the use ofMicrosoft Power Point as a means of making learning media in primaryschools.Workshop in this activity has resulted five media for elementary mathgames, namely: Card monopoly for summation, multiplication and divisiongames with a quartet cards for the third grade, the number line games, game ofplace value and game for multiplication concepts. It also generated threesimulated games with Microsoft Power Point, namely fractional Games guess,guess the name of plane, and guess the number of coins. The activity that havebeen completed, it can be said to successfully meet its objectives. One factorsupporting this success is the spirit of the elementary school teachers who areeager to improve their competence in using the method of learning a game thatutilizes the natural surrounding and simulate with computer software.